PENERAPAN METODE PEMBELAJARAN TEBAK GAMBAR UNTUK MENINGKATKAN KEMAMPUAN ANALITIS SISWA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA: ( PENELITIAN TINDAKAN KELAS DI MI X ) - Usmiati, Sri retna; faridz, mochamad; gulo, edison; A. Teluma, Yoseph Bernandino; yusuf, Rinaldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesian language learning at the elementary level often faces challenges in improving students' analytical skills. This is due to monotonous and uninteractive learning methods, which result in low motivation and activity among students during the learning process. Based on this problem, this study aims to determine the effect of applying the Guess the Picture method on improving the analytical skills of fourth-grade students at MI X. This study is a classroom action research (CAR) conducted in two cycles, involving planning, action, observation, and reflection steps. Data were collected through pre- and post-test of students' analytical skills, observation of student participation, and a questionnaire to assess students' responses to the learning process. Data analysis results showed that students' pretest scores ranged from 35 to 92, with the majority scoring around 40 and 70. After implementing the Tebak Gambar method, there was a significant improvement, with many students achieving scores above 70 and all students able to reach a higher minimum score. Additionally, observations showed that students were more active and enthusiastic during the learning process, while student responses through the questionnaire indicated they felt more interested and motivated. Based on these results, it can be concluded that the Tebak Gambar method is effective in enhancing students' analytical skills and creating a enjoyable and interactive learning environment. This study recommends the continued use of this method to improve Indonesian language learning outcomes at the elementary level. Keyword Guessing Image Method,Students' Analytical Skills, Indonesian Language Learning for Grade IV